2019
DOI: 10.1002/art.40874
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab Versus Risedronate in Glucocorticoid‐Induced Osteoporosis: Final Results of a Twenty‐Four–Month Randomized, Double‐Blind, Double‐Dummy Trial

Abstract: Objective Clinical trial results have shown that, in glucocorticoid‐treated patients, treatment with denosumab 60 mg subcutaneously once every 6 months (Q6M) increased spine and hip bone mineral density (BMD) at month 12 significantly more than treatment with risedronate 5 mg orally once daily (QD). The present analysis was performed to compare efficacy and characterize safety through month 24. Methods This phase III study enrolled men and women ≥18 years old who had received ≥7.5 mg daily prednisone or equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 43 publications
2
95
0
7
Order By: Relevance
“…These include the bisphosphonates alendronate, risedronate and zoledronic acid, teriparatide and, most recently, denosumab. 24 The evidence for efficacy of these drugs is based primarily on BMD changes and fracture prevention was not a primary outcome in any of the clinical trials. Nevertheless, some fracture data are available from secondary end-points, post hoc analyses, and observational data.…”
Section: Assessment Of Fracture Risk Should Be Performed In All Indivmentioning
confidence: 99%
See 3 more Smart Citations
“…These include the bisphosphonates alendronate, risedronate and zoledronic acid, teriparatide and, most recently, denosumab. 24 The evidence for efficacy of these drugs is based primarily on BMD changes and fracture prevention was not a primary outcome in any of the clinical trials. Nevertheless, some fracture data are available from secondary end-points, post hoc analyses, and observational data.…”
Section: Assessment Of Fracture Risk Should Be Performed In All Indivmentioning
confidence: 99%
“…28,29 In 2 other comparator randomized controlled trials, superiority of zoledronic acid and denosumab over risedronate was demonstrated for BMD end-points, but whether this translates into greater fracture protection is unknown. 24,30 Although the number of non-vertebral and hip fractures in randomized controlled trials has been insufficient to demonstrate antifracture efficacy at these sites, observational data provide some evidence for a protective effect in bisphosphonate-treated glucocorticoid users. In women aged >65 years starting glucocorticoid therapy and treated with alendronate or risedronate, Thomas et al reported that clinical vertebral and non-vertebral fracture incidence at 1 year was significantly lower when compared to the fracture incidence during the first 3 months.…”
Section: Assessment Of Fracture Risk Should Be Performed In All Indivmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with interest the article by Dr. Saag et al in which they compared the efficacy and safety of denosumab versus risedronate in glucocorticoid-induced osteoporosis (GIOP) (1). Osteoporosis in the setting of GIOP can be challenging to treat because of issues with drug adherence (due to pill burden) and the presence of multiple comorbidities.…”
Section: To the Editormentioning
confidence: 99%